Volcanic ash clouds affecting northern europe: The long view - Swindles, Graeme T.; Savov, Ivan P.; Connor, Charles B.; Carrivick, Jonathan; Watson, Elizabeth; Lawson, Ian T. (Geology Today, 2013)
The volcanic ash or 'tephra' cloud resulting from the relatively small (volume and VEI) eruption of the Icelandic volcano Eyjafjallajökull in 2010 caused major air travel disruption, at substantial global economic cost. On several occasions in the past few centuries, Icelandic eruptions have created ash and/or sulphur dioxide clouds which were detected over Europe (e.g. Hekla in 1947, Askja in 1875, and Laki in 1783). However, these historical observations do not represent a complete record of events serious enough to disrupt aviation in Europe. The only feasible evidence for this is within the geological tephra record. Ash layers are preserved in bogs and lakes where tephra deposited from the atmosphere is incorporated in the peat/mud. In this article we: 1, introduce the analysis of the Northern European sedimentary tephra record; 2, discuss our findings and modelling results; 3, highlight how these were misinterpreted by the popular media; and 4, use this experience to outline several existing problems with current tephra studies and suggest agendas for future research.